Black experiences in higher education : faculty, staff, and students - Cupid, Sherella; Tomlin, Antione D. (Contemporary issues in higher education (Charlotte, N.C.), 2023)
"Black Experiences in Higher Education: Faculty, Staff, and Students illuminates the narratives of Black faculty, staff, and students and how they navigate their professional experiences, confront the hidden curriculum and work to transform academia. As we think about the context of Black Lives Matter, intersections of race and gender, and what it means to be Black in America, there is a new consciousness and attention to the uniqueness of Black experiences in the world. This book calls attention to how Black folks are navigating their experiences within higher education. The book will present an overarching aim to delve into Black voices and experiences in higher education. Contributing authors hold varying roles of faculty, staff, and students, all sharing their experiences in higher education in the USA. In particular these scholars reflect on the challenges and opportunities within the three themes of mental health and wellness, mentorship and creating supportive spaces, and career experiences, trajectories and pathways. The aim of the variety of contributing authors creates a space to reveal unique Black experiences and voices, therefore contributing to the scholarly discourse on race in America, and in higher education, in particular"--